Ice hockey goaltenders' strategies, reaction times and anticipation times in two- and three-dimensional virtual enviroments - Tyreman, H.; Parker, J. R.; Katz, L. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Three-dimensional virtual environments are expensive to create and require specialized equipment compared with two-dimensional virtual environments, but either maybe be useful in improving reaction times, anticipation times, or strategies. This study used 10 novice and 9 expert ice hockey goaltenders. The participants were presented with 16 unique shots in two-dimensional video and again in three- dimensional video for a total of 32 shots in a realistic ice hockey goaltending situation. The order of presentation of the shots was random. The participants were asked to make saves on wrist, snap, slap, and backhand shots from both right and left handed shooters. The participants' reaction times and anticipation times were tracked with Ascension Technology Corporation's "Flock of Birds" tracking system. A flock of birds motion sensor was attached to the gloves measured positions and velocities in real tirne, which permitted the computation of reaction times and anticipation times. The differences in reaction and anticipation times were calculated from these measuremenls. All shots were high shots that needed catching or blocking. The differences in reaction and anticipation times were modeled by experience level, gender, shooter hand, shot side, participant handedness, dominate eye, shot type, goaltender style, experience in playing goal in other sports, and shot velocity.